The impact of the dyslexia label on academic outlook and aspirations: An analysis using propensity score matching - Cathryn Knight (British Journal of Educational Psychology, 2021)
BackgroundThere is current academic debate over the reliability of the dyslexia label. However, this argument does not consider the impact of the dyslexia label on an individual’s academic outlook and aspirations.AimsUsing data from the Millennium Cohort Study, this paper aims to objectively explore the impact of the dyslexia label on academic outlook and aspirations.MethodsPropensity score matching was used to compare children with dyslexia with a non-dyslexic group matched on ability, socioeconomic class, parent education, income, country, gender, and age in year group.ResultsThe results show that those labelled with dyslexia hold lower beliefs about their ability in English and Maths than their matched peers without this label. The children labelled with dyslexia were also significantly less likely to say that they would go to university. Furthermore, teachers and parents held lower aspirations for children labelled with dyslexia. As the children were matched, the results show that dyslexic children, their teachers and parents hold lower expectations of the child’s academic ability while holding higher expectations of those with matched characteristics who do not have the dyslexia label.ConclusionsThe paper concludes that caution is needed when labelling with dyslexia and that further research is needed in order establish whether labelling with dyslexia is beneficial in the current system.